Romantic Motives in the Lithuanian Partisan and Deportee Songs - Nakienė, Austė (Tautosakos darbai, 2021)
The aim of the article is revealing the manifestations of romanticism in the songs created during and after the World War II by the partisans and their supporters, political prisoners and deportees. The author employs studies by Vytautas Kubilius and other literary scholars; however, her research is a folkloristic one, since the songs’ lyrics are perceived as a layer of folklore created at a definite period and characterized by the common stylistic features. Having noted a coherent continuation of the tradition of national romanticism, the author suggests defining the new wave of this style originating in the postwar period as folk romanticism. This folk romanticism blossomed precisely at the time when anti-romantic tendencies prevailed in the public artistic expressions. National culture was suppressed in the occupied Lithuania, and its famous creators silenced. Therefore, the idealist creativity moved to the underground, while traditional national and romantic motives were further developed in the illegal publications by the partisan movement and in the orally spread folksongs. The great representative of the 19th century literary romanticism Maironis established the high style of the Lithuanian poetry; notions prevailing in his poems express the most cherished values, including the glorious past, noble ideals, honor, struggle, and unity. According to Vytautas Kubilius, “the high style shaped by Maironis affected the Lithuanian cultural worldview: several generations used his poems to appreciate the nature and the past of the native country, learned of loving, believing and endurance in the center of the historical whirlwinds” (Kubilius 1993: 145). The return of the romantic ideals of the 19th century in the middle of the 20th century is hardly surprising, since it is only natural in the war and postwar times – the critical period again required resistance and defense from the literature and poetry. The songs created during war and postwar period harbor almost all the typical romantic literary motives. They exalt the beauty of the homeland praising its green villages, winding rivers with meadow banks, the roadside crosses, and faraway woods. These motives are often entwined with those of spring, blossoming, and youth. The native country is frequently portrayed in the songs of resistance as a beloved girl with a “rue spray in her hair” and as a mother taking care of her children. In the songs’ lyrics, there are harsh winds blowing, thunders striking, falcons taking up to the skies notwithstanding, and one is led to hope for the dawn, sunrise, and the glorious morning of freedom. The liberated Lithuanian capital with a tricolor flag blowing out above the Gediminas’ Castle is also often depicted. The motive of Lithuanian woods, or green forests is especially prominent both in the romantic literature and in the postwar folksongs. From ancient times, the woods used to protect Lithuanians against their enemies; during the postwar period, they also served as the only shelter for people prosecuted by the fierce regime. As noted by the folklore researcher Kostas Aleksynas, a huge number of patriotic songs has been created in the course of a comparatively short period of the armed national resistance (Aleksynas 2009: 7), the folksong creativity seemingly acquiring new powers. The continuation of the national romanticism and elaboration of numerous motives employed by the Lithuanian poets analyzed in this article could perhaps explain this phenomenon. Composition of the new folksongs did not require forming of a new poetic language, since the well-established romantic tradition presented itself to use, and only certain appropriate motives had to be selected.